1990
DOI: 10.1007/bf02897227
|View full text |Cite
|
Sign up to set email alerts
|

Brain uptake and anticancer activities of vincristine and vinblastine are restricted by their low cerebrovascular permeability and binding to plasma constituents in rat

Abstract: Unidirectional blood-brain barrier transfer of the lipophilic anticancer agents vincristine and vinblastine was studied in anesthetized rats, using an isolated, in situ brain perfusion technique. Drug binding to plasma constituents was also measured. Despite the high lipophilicity of these agents (the log octanol/physiological saline partition coefficient equalled 2.14 and 1.68, respectively), the cerebrovascular permeability-surface area product, PA, of vincristine in plasma was only 0.49 x 10(-4) ml s-1 g-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(30 citation statements)
references
References 25 publications
3
27
0
Order By: Relevance
“…The in situ rat brain perfusion data correlated well with our in vitro permeability data, showing that Tx-67 permeation across the BBB was in fact substantially greater than the permeation of Taxol into rat brains. Our Taxol data were comparable to perfusion data for other anticancer drugs such as vincristine and vinblastine (Greig et al, 1990).…”
Section: Discussionsupporting
confidence: 74%
“…The in situ rat brain perfusion data correlated well with our in vitro permeability data, showing that Tx-67 permeation across the BBB was in fact substantially greater than the permeation of Taxol into rat brains. Our Taxol data were comparable to perfusion data for other anticancer drugs such as vincristine and vinblastine (Greig et al, 1990).…”
Section: Discussionsupporting
confidence: 74%
“…Levin has estimated the threshold of lipid-mediated transport through the BBB as being between 400 and 657 Da (43). This threshold was corroborated by Grieg and coworkers (44), who showed that vincristine or vinblastine have BBB permeability coefficients that are much reduced compared to what would be expected based on the lipid solubility of these compounds, which have a molecular weight of 814-825 Da. Another example is cyclosporin which has a molecular weight of 1200 ( Fig.…”
Section: Small Molecule Transport Through the Blood-brain Barriermentioning
confidence: 56%
“…tered systemically [13,25,26]. A major determinant for a water-soluble agent is its cerebrovascular permeability, in the absence of a facilitated transport mechanism [27].…”
Section: Discussionmentioning
confidence: 99%